Anti-Driving While Intoxicated Device (Anti-DWI Device) - Rusli, Ahmad Najmie; Rasdi, Nurul Nadiah; Mustar, Muhammad Fadil (2020)
Driving while intoxicated (DWI) caused by alcohol can increase the risk of a road accident. This is because a drunk driver is 13 times more likely to cause a road accident compared to a sober one. The cases of road accidents due to DWI have risen alarmingly and the consequences are dire that includes minor injury, major injury, or even death towards the driver, passengers, or pedestrians. To prevent road accidents, a solution needs to be done before the driver operates the motor vehicle. So, the objectives of this project is to design and develop a prototype device called Anti-Driving While Intoxicated Device (Anti-DWI Device). This device can detect the alcohol level, temperature, and heart rate of a person before driving. These three stimulants will be detected by three sensors and these sensors are controlled by a microcontroller that applies Arduino code. When the person exhibits the signs of intoxication, the engine of the motor vehicle will not start. A message will then be sent to a registered family member to inform of the situation as to make certain the intoxicated person can get home safely. Consequently, it will prevent the driver from driving and curb road accidents from happening. This situation will not only benefit the driver but also other people on the road in terms of safety. Overall, the result of designing and developing the prototype device is successful.